Beneficial Microbes: The pharmacy in the gut. Issue 1 (2nd January 2016) - Linares, Daniel M.; Ross, Paul; Stanton, Catherine
ABSTRACT: The scientific evidence supporting the gut microbiome in relation to health maintenance and links with various disease states afflicting humans, from metabolic to mental health, has grown dramatically in the last few years. Strategies addressing the positive modulation of microbiome functionality associated with these disorders offer huge potential to the food and pharmaceutical industries to innovate and provide therapeutic solutions to many of the health issues affecting modern society. Such strategies may involve the use of probiotics and prebiotics as nutritional adjunct therapies. Probiotics are generally recognized to be a good form of therapy to keep harmful, intestinal microorganisms in check, aid digestion and nutrient absorption, and contribute to immune function. Probiotics are reported to improve microbial balance in the intestinal tract and promote the return to a baseline microbial community following a perturbing event (dysbiosis) such as antibiotic therapy. Prebiotics are selectively fermented ingredients that allow specific changes, both in the composition and/or activity in the gastrointestinal microflora, which confers benefits upon host well-being and health.